Statistical azimuthal structuring of the substorm onset arc: Implications for the onset mechanism. Issue 5 (4th March 2017) - Kalmoni, N. M. E.; Rae, I. J.; Murphy, K. R.; Forsyth, C.; Watt, C. E. J.; Owen, C. J.
Abstract: The onset of an auroral substorm is generally thought to occur on a quiet, homogeneous auroral arc. We present a statistical study of independently selected substorm onset arcs and find that over 90% of the arcs studied have resolvable characteristic spatial scales in the form of auroral beads. We find that the vast majority (~88%) of auroral beads have small amplitudes relative to the background, making them invisible without quantitative analysis. This confirms that auroral beads are highly likely to be ubiquitous to all onset arcs, rather than a special case phenomena as previously thought. Moreover, as these auroral beads grow exponentially through onset, we conclude that a magnetospheric plasma instability is fundamental to substorm onset itself. Key Points: The overwhelming majority of seemingly homogenous substorm onset arcs have characteristic azimuthal spatial structuring Characteristic spatial scales of these auroral beads are quantitatively calculated in the range 80–105 km in the ionosphere Consistent structuring of the onset arc is compelling statistical evidence that a plasma instability is a critical component of the substorm